1956
DOI: 10.1021/j150544a029
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of the 17 Isomeric Hexenes.of the API Research Series

Abstract: For the isomeric hexenes, highly purified hydrocarbons of the API Research series, the following properties were measured : densities a t 20,25 and 30"; refractive indices a t seven wave lengths at 20,25 and 30" and boiling points and vapor pressures a t 80 to 780 mm. The data on refractive indices were correlated by means of modified Cauchy and Hartmann equations, and values of the constants are given for each compound, to ermit precise evaluation of the refractive index as a function of wave length. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Usually the agreement between measurements made at Bartlesville and those of Rossini's group is within a few tenths of 1%, but not in this case. Camin and Rossini (1956) note that their sample was (99.85 ( 0.13) mol % pure. The sample used in this research was analyzed by CGC using both a polar and a nonpolar column and was shown to be >99.95 mol % pure.…”
Section: -Methylpent-1-enementioning
confidence: 95%
See 2 more Smart Citations
“…Usually the agreement between measurements made at Bartlesville and those of Rossini's group is within a few tenths of 1%, but not in this case. Camin and Rossini (1956) note that their sample was (99.85 ( 0.13) mol % pure. The sample used in this research was analyzed by CGC using both a polar and a nonpolar column and was shown to be >99.95 mol % pure.…”
Section: -Methylpent-1-enementioning
confidence: 95%
“…Figure 6 compares sets of vapor pressure measurements on 4-methylpent-1-ene reported in the literature (Schmitt and Boord, 1932;Boord et al, 1949;Camin and Rossini, 1956;Martire and Pollara, 1965;Vera and Prausnitz, 1971;Daubert et al, 1994) with values obtained using the Wagner equation and the parameters listed in Table 10. Agreement between the measurements is relatively poor.…”
Section: -Methylpent-1-enementioning
confidence: 99%
See 1 more Smart Citation
“…Second, only small organic and inorganic molecules for which accurate formation enthalpies are known have been used to equilibrate the reactions (i.e., were used as A, B, and D in eq ), in particular acetylene, ethylene, ethane, CO, methane, H 2 , H 2 O, H 2 S, HCN, N 2 , and NH 3 . We expect under these conditions that the possible cancellations of errors are minimal, and better insights into the ability of the electronic structure theory methods to provide accurate reaction enthalpies can be gained. …”
Section: Computational Detailsmentioning
confidence: 99%
“…Table 3. Majer andSvoboda, 1985. b Lebedev andMiroshnichenko, 1993. c Camin and Rossini, 1956. d Lister, 1941.…”
Section: Discussion and Data Reductionmentioning
confidence: 99%